2014
DOI: 10.3133/ofr20141038
|View full text |Cite
|
Sign up to set email alerts
|

Passage and survival probabilities of juvenile Chinook salmon at Cougar Dam, Oregon, 2012

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Suggested citation: Beeman, J.W., Evans, S.D., Haner, P.V., Hansel, H.C., Hansen, A.C., Smith, C.D., and Sprando,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The pattern we observed offered an opportunity for directed adaptive management, whereby managers took action in 2013 to minimize the reintroduction of immigrants (the LSDR method). These measures were taken due to the low recruitment rate estimates (CRRs) provided by our study and interest to limit the impacts of poor juvenile passage through the dam (Beeman et al ., ) to only those salmon associated with past reintroduction. One year's results suggested that this method successfully reduced the trap and transport of immigrants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pattern we observed offered an opportunity for directed adaptive management, whereby managers took action in 2013 to minimize the reintroduction of immigrants (the LSDR method). These measures were taken due to the low recruitment rate estimates (CRRs) provided by our study and interest to limit the impacts of poor juvenile passage through the dam (Beeman et al ., ) to only those salmon associated with past reintroduction. One year's results suggested that this method successfully reduced the trap and transport of immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…The low CRRs may also be due to the low survival rate to sexual maturity for Chinook salmon [e.g. Smolt‐to‐adult ratios (range: 0–2.2) Claiborne et al ., ] because there are many sources of mortality, such as poor passage through dams (Beeman et al ., ), predation (Collis et al ., ; Sinclair & Zeppelin, ), starvation during outmigration to the ocean (Kareiva, ) or while foraging in the open seas (Parker, ) and mortality prior to spawning (Keefer et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no assisted downstream passage for juveniles produced above the dam. Downstream passage of outmigrants through Cougar Reservoir and Dam is associated with high mortality (Beeman et al., 2014; Duncan, 2011; Monzyk et al., 2015; Romer et al., 2016), and is likely a key factor limiting recovery (ODFW and NMFS, 2011). Productivity of the reintroduced population has been continuously evaluated since 2007 using genetic parentage analysis.…”
Section: Methodsmentioning
confidence: 99%